1985
DOI: 10.1128/aac.27.5.806
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibilities of 126 clinical isolates of Yersinia enterocolitica to 21 beta-lactam antibiotics

Abstract: The MICs of 21 P-lactam antibiotics were measured against 126 clinically significant and epidemiologically unrelated Yersinia enterocoEltica isolates. The most active antimicrobial agents tested (geometric means of MICs) were ceftriaxone, cefotaxime, ceftizoxime, and cefmenoxime (0.06 to 0.08 ,ug/ml). Mezlocillin (1.36 ig/ml) and piperacillin (1.57 ,ug/ml) were the most active penicillins. Aztreonam (5, 8-11, 17, 21, 30, 31), and the entire species was considered to be resistant to these 1-lactam antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…Yersinia enterocolitica (mostly biotypes 1B, 2, 3, 4, and 5) is naturally resistant to some ␤-lactams, such as penicillins (ampicillin, amoxicillin, and ticarcillin) and first-generation cephalosporins (cephalothin and cephalexin), but it remains susceptible to cefuroxime and oxyimino-␤-lactams (142)(143)(144). Synergy is usually detected with combinations of ticarcillin or carbenicillin and clavulanate, rather than with amoxicillin plus clavulanate, which is inactive against the second chromosomal ␤-lactamase (cephalosporinase/BlaB).…”
Section: Toca P Vulgaris R Aquatilis and S Fonticola)mentioning
confidence: 99%
“…Yersinia enterocolitica (mostly biotypes 1B, 2, 3, 4, and 5) is naturally resistant to some ␤-lactams, such as penicillins (ampicillin, amoxicillin, and ticarcillin) and first-generation cephalosporins (cephalothin and cephalexin), but it remains susceptible to cefuroxime and oxyimino-␤-lactams (142)(143)(144). Synergy is usually detected with combinations of ticarcillin or carbenicillin and clavulanate, rather than with amoxicillin plus clavulanate, which is inactive against the second chromosomal ␤-lactamase (cephalosporinase/BlaB).…”
Section: Toca P Vulgaris R Aquatilis and S Fonticola)mentioning
confidence: 99%
“…The availibility of selective media and comprehensive identification and biotyping schemes contributed further to the detection of Y. enter ocolitica in stool specimens. Results of in-vitro antimicrobial susceptibilty testing of 7. enter ocolitica from different countries have been reported in several studies (Hornstein et al, 1985;Hoogkamp-Korstanje, 1987;Pham, Bell & Lanzarone, 1991a).…”
Section: Introductionmentioning
confidence: 99%
“…Newer P-lactam antibiotics were suggested as alternatives in severe Yersinia-infections (20,21,32,37). However, an animal model showed that the treatment of mice infected by Y. enterocolitica failed with the newer P-lactams despite in vitro susceptibility of the strain (31).…”
mentioning
confidence: 99%